Caracterização de bovinos de corte da raça canchim por meio de assinaturas de seleção. - Duarte, Igor Nelson Herculano (2020)
Genomic analyses have been widely used in livestock and molecular markers has enabled the identification of selection signature in the bovine genome, which are regions associated with traits under selection and that present an increase in allele frequencies in certain loci. Thus, the aim of this study was to identify and characterize selection signatures present in Canchim (CA) animals considering information on the genotypes of the founders breeds Nelore (NE) and Charolais (CH). High-density SNP genotypes (single nucleotide polymorphism) were considered for 395 CA animals (population of interest), 814 NE animals and 897 CH animals (reference populations). After quality control and genotype imputation, 693,531 SNPs (CA vs. NE) and 707,626 SNPs (CA vs. CH) remained for identification of selection signatures using the XPEHH and Rsb methodologies (based on the extended haplotype homozygosity between populations) and Fst (allele fixation index). Selection signatures were defined as SNPs that had the 50 highest positive sign values for each methodology. Among the various regions identified as selection signatures in Canchim cattle, a large part was related to the traits that are the main selection objectives for beef cattle, such as weight gain and meat quality, as well as reproductive traits. The identification of selection signatures putatively associated with the morphology, immunity, behavioral traits and circadian rhythm have given new perspectives for understanding the genetic architecture present in the Canchim. It was possible to verify how the contribution of the founding breeds (NE and CH) helped to shape the genetic composition present in Canchim, as well as to understand which regions effectively contribute to the genetic variability of the breed. These results may assist in directing the genetic evaluation program of Canchim.